FOR SILK INDUSTRY ENTERPRISES: DEVELOPMENT OF AN IMPROVED MODEL OF PDCA CYCLE: FOR SILK INDUSTRY ENTERPRISES: DEVELOPMENT OF AN IMPROVED MODEL OF PDCA CYCLE - Qakhramonov, Mukhammadali; Khosimov , Akhtamhon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
While modern techniques and technologies play an important role in the development of silk industry enterprises, the introduction of internationally recognized standards and management systems is an urgent issue. The PDCA (Plan, Do, Check, Action) cycle is a quality management system widely used in the industry as a continuous improvement tool, and the possibilities of introducing this improved model to silk enterprises are highlighted. Therefore, the process approach PDCA cycle, which is available in the quality management system that is internationally recognized and meets international requirements, is currently necessary in the silk industry enterprises. In this article, we recommend the development of a PDCA cycle based on the requirements of the quality management system for silk industry enterprises and the introduction of modern requirements for the quality system. As a first step, the scientific work carried out in the direction of the quality management system was reviewed, and the changes that occurred after the introduction of the PDCA cycle in silk enterprises were carefully analyzed. All documents of silk enterprises have been subjected to regulatory expertise and approved by the department's management. Conclusions, scientific proposals and practical recommendations were presented on the formation of healthy competition in the enterprises of the silk industry by improving the PDCA cycle of the quality management system.